Gastric Perforation Caused by an Intragastric Balloon: Endoscopic Findings - In Kyung Yoo; Hoon Jai Chun; Yoon Tae Jeen (Korean Society of Gastrointestinal Endoscopy, 2017)
Intragastric balloon (IGB) insertion has been most frequently used in the West as an effective endoscopic treatment for morbid obesity, in practice. Recently, there is a growing number of cases requiring IGB deployment for obesity treatment in Korea. One of the reported complications of IGB use is gastric perforation. A 47-year-old woman was admitted to the hospital with mild symptoms, 7 weeks after having an IGB placed. Esophagogastroduodenoscopy was performed and gastric ulcer perforation was observed in the ulcer base, where food particles were impacted. Laparoscopic primary repair was done successfully. This was a case of gastric perforation, secondary to poor compliance with a proton-pump inhibitor (PPI). PPI and Helicobacter pylori eradication are important for ulcer prevention following IGB deployment.